Barkhausen noise signal analysis of heat treated samples at various magnetising frequencies - Srivastava A.; Kumar H.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Signal processing of magnetic Barkhausen noise was performed to reveal the useful information content of the signal which would otherwise difficult due to stochastic nature of the signal. Magnetic Barkhausen noise signal was measured from different heat treated steel samples which were further processed to investigate the effect of heat treatment on Barkhausen noise signal. The dependence of Barkhausen signal upon magnetising frequency was also discussed in terms of RMS value of Barkhausen noise envelope. Variation in the RMS value of the Barkahusen noise profile with magnetising frequency and mechanical properties was explained using micromagnetic theory. The present study shows that magnetic Barkhausen noise signal depends upon mechanical properties as well as on magnetising frequency which needs to be optimised in order to use magnetic Barkhausen noise as a characterisation tool. © 2018 Inderscience Enterprises Ltd.